The Importance of Demographic Characteristics of Substance Use Disorders of University Students - DEMİRARSLAN, Esra; ARABACI, Zeynep; ÇAĞLAR, Atila (Gumushane University, 2023)
Substance use disorders (SUDs) have been linked to physical and mental health problems as well as socioeconomic impacts which can also affect the perioperative period. This study aimed to analyze the SUDs rates and sociodemographic characteristics of university students. The population of the study included 12,841 students who were enrolled in the university in the 2012-2013 academic year. The sample included 1,284 students continuing education on the campuses of the university. The sample represented 10.0% of the research population, and its participants were selected using easy sampling. For the statistical analysis, the study used descriptive statistics as well as the Kolmogorov-Smirnov test, Chi-Square, ANOVA, and the Games-Howell posthoc test. Of the participants, 60.4% reported SDU at least once. The onset of substance use (SU) was younger than 15 years old. The female students reported a higher rate of SU than the male students. Marijuana was the first substance that the participants declare that they tried at least one substance. The participants who reported SDU had low academic grade averages. The rate of SUDs increased when the students had substance users around them and peer influence was immense. The study results suggest that the migration effects of universities should be studied.
Keywords: 4. Education; 10. No inequality; 16. Peace & justice; 3. Good health